Bioecological and Ecotourism Development Strategy of Whale Shark-Rhincodon Typus in Teluk Cenderwasih National Park - Murdani, Nanang Hari; Masyud, Burhanuddin; Yulianda, Fredinan (Media Konservasi, 2018)
A study on whale sharks have been carried out in Teluk Cenderawasih National Park (TCNP) on May-June 2014. The objectives of this studywere to analysis bioecological of whale shark, the perceptions of local communities and tourists on whale shark ecotourism development and toformulate the ecotourism development strategy in TCNP. Data were collected through observations and and counting the number of whale sharks,gender identification and age categories, and estimation of body length; measurement of some environmental variables (sea surface temperature,salinity, sea brightness); and regarding their perception of whale sharks as objects of tourist attraction. The result showed that the generally thewhale sharks come to the surface in waters that there are many bagan fisheries that many fish in the net. Whale sharks feed and come to the surfacein the fishing platform in the morning until noon with a duration of 15-30 minutes. Physical enviroment conditions of sea in TCNP were temperatures28-31°C; salinity 33-34‰ and sea brightness 7-12 m. The total number of the emergence of the whale sharks was 30 times and identified as 15animals, all young males, measuring between 3 and 6 m, generally do not have injuries. The perseptions of local communities about development ofwhale shark ecotourism were positive and will be supported this program. Generally, most tourists, of which 87,88% of them were foreigners, gavepositive perceptions on whale shark attractions in TCTN, from attractive to very attractive, although there are some aspects of travel managementsthat need to be improved, such as the availability of information services, tourist guides, and the comfort level. Some development strategies must bedone, i.e. continuous monitoring of whale shark, human resource capacity building, provision of tourist support infrastructure, coordination andsynergy with stakeholders, and increase public awareness and the development of cultural tourism attractions as an integrated ecotuorism program.Keywords: bioecological, ecotourism, development strategy, Teluk Cenderwasih National Park, whale shark